O processo de trabalho dos Agentes Comunitários de Saúde : dilemas entre o trabalho prescrito e o trabalho real - Ribond, Michelle Garcia de Alcântara (2014)
The CHA operates in groups of FHS developing various activities, such as registration of families, construction site diagnosis, mapping the territory of health, identification small risk areas, conduct home visits and collective and intersectoral actions in health education. This singular action makes the CHA‟s job different from other workers in the health field. We analyzed the CHA‟s working process of two teams FHS of Cariacica - ES, aiming to understand the differences between the prescribed work and the actual work in FHS‟s daily. This is a descriptive study with qualitative and ethnographic approach to data collection through the techniques of systematic observation and documentary research. We collected the description of the actual work through the data recorded in a field diary, and the job description prescribed by the 27 documents found. The research highlights the CHAare not able to perform all prescribed activities, because of the amount of standards, technical manuals, books, etc, that guide their work, in reason that they still not have a permanent or continuing education to facilitate the understanding of all such materials. However, this situation is not meaning that the work of the CHA is not being well done in accordance with the proposal of Primary Care. Although these professionals can‟t do all of prescribed work, they can go beyond the requirements with creativity, good sense, affection, community liaison and desire to transform the reality they live in, building their own way of “being and work" as a community health agent, that is not described in standards and manuals, but it is the reflection of a humanized care, focused in the family and reality of that territory.